Penggunaan LKS Berbasis Inkuiri Terbimbing pada Materi Momentum dan Gerak Harmonik Sederhana Untuk Peningkatan Kompetensi Fisika Siswa - Hayatul Islamiah; Hidayati Hidayati; Zulhendri Kamus (Universitas Negeri Padang, 2018)
Today, learning resource can’t to support learning activities of student. Besided, exsperiment activities just demonstrasion in front of the class by teacher, so that learning has not been student centered. One of the learning resources that can help student activity is by using Student Worksheets or as we known as LKS. Worksheets are integrated with the scientific approach and the guided inquiry learning model.This research find the effect students worksheet which based guided inquiry to students competence of physics class X in SMAN 1 Pariaman. The type research is quasi experiment and nonequivalen control group design. The population of this research is all students grade X MIPA in SMAN 1 Pariaman that listed in 2017/2018 years . There are three steps in this research, those are preparation, implementasion, and completion. Nontest data is is obtained from the sheet’s self assessment, sheet’s friend’s assessment and sheet’s performence in laboratorium. Test data is result of students final test. The average of the using students worksheet based guided inquiry in knowledge competence 83,42, the attitude competence is 79,53, on the skill competence is 86,31. The result of average value obtained by students can be concluded that there effect in the using of student worksheet based guided inquiry can be improve students physics competence in class X SMAN 1 Pariaman.